2017
DOI: 10.1088/1367-2630/aa8a5d
|View full text |Cite
|
Sign up to set email alerts
|

A mass-independent conformal quantum cloak

Abstract: An obstacle to constructing a quantum cloak with the transformation design method for steering a matter wave is the device involving the anisotropic modulation of the particle mass. It is the purpose of this paper to show that a narrow-acceptance-angle quantum cloak generated by a kind of conformal mapping could be mass-independent. This greatly simplifies the construction of the device since it can now be finished only by applying a potential field to a region of the shell. As demonstrations of the conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A similar means to the construction of the invisibility cloak for the matter wave can interpret the transformation structure as the anisotropic mass parameter and an effective scalar potential [10]. Recently, it was reported that using conformal mapping to design a quantum device for splitting a matter wave only needs to offer a scalar potential in the controlling region without resorting to the modulation of mass [11] . It largely simplifies the construction of the transformation device.…”
Section: Physical Realization Of the Conformally Geometric Effectmentioning
confidence: 99%
“…A similar means to the construction of the invisibility cloak for the matter wave can interpret the transformation structure as the anisotropic mass parameter and an effective scalar potential [10]. Recently, it was reported that using conformal mapping to design a quantum device for splitting a matter wave only needs to offer a scalar potential in the controlling region without resorting to the modulation of mass [11] . It largely simplifies the construction of the transformation device.…”
Section: Physical Realization Of the Conformally Geometric Effectmentioning
confidence: 99%
“…Through the reinterpretation of the geometric structure of the transformation as the material properties, the method enables novel devices such as invisibility cloaks (e.g., [4]). Recently, researchers have been interested in the applications of transformation design to the steering of matter waves (e.g., [5,6]). Due to the interaction nature of the quantum particle with external fields, the concept of the transformation design in quantum physics could exhibit more fertile content such as leading us to reveal new quantization systems (e.g., [7]) and more general monopole fields [8].…”
Section: Introductionmentioning
confidence: 99%